Sensory Properties of Yogurt Dairy and Yogurt Goat's with Added Edamame - Hasanah, Niswatin; Musi, Ngani Alwirya (P3M Politeknik Negeri Jember, 2024)
This study aims to determine the effect of adding edamame on the sensory properties (level of sweetness and aroma of edamame) cow's and goat's milk yogurt. The experiment was carried out using a completely randomized design (CRD) with 5 treatments and 3 replications consisting of, P0 = without the addition of 0% edamame, P1 = the addition of 5% edamame, P2 = the addition of 10% edamame, P3 = the addition of 15% edamame, P4 = 20% edamame addition. The data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) with a level of 5%. The results showed that the addition of edamame to cow's and goat's milk yogurt showed significant differences (P<0.05) on the aroma of edamame and the level of sweetness in yogurt. The addition of 5% edamame to cow's and goat's milk yogurt was the lowest average of 2.05-2.01 with the criteria of not smelling of edamame, while the highest average was the addition of 20% edamame, namely 3.35 and 3.36 with the criteria somewhat smell of edamame. The lowest average sweetness level for cow's and goat's milk yogurt with the addition of 5% edamame was 2.18 and 1.75 with criteria not very sweet and not sweet, while the highest average with the addition of 20% edamame was 3.15 and 3.08 with a rather sweet criteria.